Effects of Ramadan Fasting on Ambulatory Blood Pressure in Hypertensive Patients - Maryam Alinezhad Namaghi; Mahdi Hasanzadeh Dalooe; Mohsen Nematy; Amir Hosein Khoshnasab; Adeleh Khoshnasab; Javad Farrokhi; Abdolreza Norouzy (Journal of Fasting and Health, 2014)
Background: Previous studies have indicated that Ramadan fasting has beneficial effects on cardiovascular risk factors, specially blood pressure and heart rate (1). In the present study, the effect of Ramadan fasting on 24-hour ambulatory blood pressure and heart rate has been investigated. Materials and Methods: This prospective observational study was conducted on two groups of individuals. Six patients under hypertension treatment were allocated to the case group and 12 healthy individuals were selected as the control group. Twenty-four-hour blood pressure monitoring was carried out during four periods: prior to Ramadan, during the first ten days and the last ten days of Ramadan, and one month after it. All patients continued their medication, which was administered twice per day. Twenty-four-hour mean blood pressure, weight, body mass index (BMI), and waist circumference were compared among the groups. Results: In the case group, there was a significant reduction in subjects’ weight during the third period of the experiment; also, a significant improvement was observed in the heart rate during the second and third periods in the case group (P<0.05, t-test). Conclusion: This study indicated a significant improvement in the subjects’ heart rate over second and third periods of measurements; also, no high-risk variations in blood pressure or heart rate were observed among the subjects.